2021
DOI: 10.1186/s12884-021-04119-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient decision aid for trial of labor after cesarean (TOLAC) versus planned repeat cesarean delivery: a quasi-experimental pre-post study

Abstract: Objective To assess the impact of a web-based decision aid on patient-centered decision making outcomes among women considering a trial of labor after cesarean (TOLAC) versus planned repeat cesarean delivery. Methods The Birth Decision Aid Study (B-READY) was a quasi-experimental pre-post study of two sequential cohorts. From June 18, 2018 to July 31, 2019, 50 women were enrolled in routine care, followed by 50 women who were enrolled in the decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…34 In addition, this meta-analysis concluded that treatment of gestational diabetes could reduce the risk of macrosomia by half (relative risk: 0.50) and, in turn, shoulder dystocia (relative risk: 0.42). 34 With regard to mode of delivery, shared decision making is reasonable, 35 including a discussion of the risks and benefits of labor and vaginal birth and risk of shoulder dystocia. The low frequency of shoulder dystocia-related trauma even at high infant birth weights and the high frequency of cesarean deliveries for individuals with suspected high birth weight infants prenatally likely results in many unnecessary cesarean births, regardless of diabetes status.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, this meta-analysis concluded that treatment of gestational diabetes could reduce the risk of macrosomia by half (relative risk: 0.50) and, in turn, shoulder dystocia (relative risk: 0.42). 34 With regard to mode of delivery, shared decision making is reasonable, 35 including a discussion of the risks and benefits of labor and vaginal birth and risk of shoulder dystocia. The low frequency of shoulder dystocia-related trauma even at high infant birth weights and the high frequency of cesarean deliveries for individuals with suspected high birth weight infants prenatally likely results in many unnecessary cesarean births, regardless of diabetes status.…”
Section: Discussionmentioning
confidence: 99%
“…Because of shared decision-making, only 60–80% of TOLAC patients have successful VBAC. Another issue that contributes to difficulties in selecting a mode of delivery after CS is that women do not understand the advantages and disadvantages of each mode of delivery; this can be attributed to a lack of counseling [ 9 , 35 , 39 ]. Therefore, mothers should be counseled, the development of a decision model is critical, and the information provided should be updated scientifically [ 12 , 40 ].…”
Section: Discussionmentioning
confidence: 99%